Exhibition and Surveillance on the Internet: A Critical Reading - Güler Demir (Türk Kütüphaneciliği)
The internet, new media, and social media environments should not be assessed only in terms of conveniences and opportunities that offer within the framework of technology. Along with the positive properties of these environments, there also exist negative aspects of carrying risks, and that may lead to problems. Despite the positive properties such as interaction, sharing, speed, flexibility and convenience, that might also be approached as a global network allowing negativities such as displaying, surveillance, inspection, and profiling. The negativities as mentioned earlier might lead to unrecoverable scientific, socio-economic, psychosocial, social and other consequences. The book “Exhibition and Surveillance on the Internet: a critical reading” by Mukadder Çakır is a thought-provoking book which brings many significant approaches to the internet environment and its tools in a critical context.